Urea-SCR technology for deNOx after treatment of diesel exhausts - Tronconi, Enrico; Nova, Isabella (Fundamental and Applied Catalysis,, 2014)
Urea-SCR Technology for deNOx After Treatment of Diesel Exhausts presents a complete overview of the selective catalytic reduction of NOx by ammonia/urea. The book starts with an illustration of the technology in the framework of the current context (legislation, market, system configurations), covers the fundamental aspects of the SCR process (catalysts, chemistry, mechanism, kinetics) and analyzes its application to useful topics such as modeling of full scale monolith catalysts, control aspects, ammonia injections systems and integration with other devices for combined removal of pollutants.